Ratio Kadar Ldl/Hdl Tikus Putih Sprague Dawley Hiperlipidemia Setelah Diberi Cangkang Udang Laut (Penaeus monodon F.) - Isdadiyanto, Sri (Bioma : Berkala Ilmiah Biologi, 2015)
The objective of this study was to analyze the ratio of LDL/HDL level of Sprague Dawley rats induced by high fat ration after given of sea shrimp carapace (Penaeus monodon F.). The animals for this study were twenty adult male rats divided into four groups, i.e. group I as the control was fed with basal ration containing normal fat for 3 months, group II was fed ration containing high fat for 3 months, group III was fed ration containing high fat and given sea shrimp carapace 180 mg per kg body weight per day orally in 2 ml aquadest for 3 months, group IV was fed ration containing high fat for 3 months and after 1 month given sea shrimp carapace 180 mg per kg body weight per day orally in 2 ml aquadest for 2 months. Each group consisted of five animals. After 90 days, the rats were necropsied and the blood were collected to analyzes ratio of LDL/HDL level. LDL level and HDL level were measured using colorimetric enzymatic method and Roche/Hitachi cobas c systems automatically calculate. Â The difference between treatments was statistical analysis by Anava, and continued by Lowest Significant Difference Test to locate the difference. The result showed that high fat diet increased ratio of LDL/HDL level and Sea shrimp carapace decreased ratio of LDL/HDL level. Â  Keywords: Sea shrimp carapace, Sprague Dawley rats, ratio of LDL/HDL level